Circular economy awareness of students in higher education: the assessment of knowledge, attitudes, and behavior - Wardani, Dewi Kusuma; Sabandi, Muhammad; Kardiyem, Kardiyem; Indira, Fransisca Rahcmawati (Journal of Education and Learning (EduLearn), 2025)
The implications of the circular economy system are important in creating a balance of sustainable economic activities. This study aims to analyze student awareness as agents of change towards circular economy principles and practices in terms of knowledge, attitude, and behavior (KAB) variables based on a gender perspective and the correlation between variables. The study used a descriptive quantitative approach with a survey method via a Google form questionnaire. Research data was collected from June to August 2023. The study population composed of active students of economics/cooperative education programs, office administration education, and accounting education batches of 2020 and 2021 at Universitas Negeri Semarang (UNNES) and Universitas Sebelas Maret (UNS) with a research sample of 245 students. Result showed that average circular economy awareness score did not differ significantly between men and women, and an analysis revealed a positive correlation between the variables of knowledge and behavior, knowledge and attitudes, and attitudes and behavior. The study's result demonstrates that knowledgeable students will develop a favorable attitude about the effects of the circular economy and pro-environmental behavior.